Androgen receptor in satellite cells is not essential for muscle regenerations. (29th July 2020) - Michaelis, Martin; Sakai, Hiroshi; Sato, Takahiko; Kanagawa, Motoi; Fukada, So-ichiro; Imai, Yuuki
Abstract: The anabolic effects of androgen on skeletal muscles are thought to be mediated by androgen receptor (AR). Although multiple studies concerning the effects of AR in males have been performed, the molecular mechanisms of AR in skeletal muscles remain unclear. Here we first confirmed that satellite cells from mouse hindlimb muscles express AR. We then generated satellite cell-specific AR knockout mice using Pax7 CreERT2 and AR L2/Y mice to test whether AR in satellite cells is necessary for muscle regeneration. Surprisingly, we found that muscle regeneration was compromised in both Pax7 CreERT2(Fan)/+ control mice and Pax7 CreERT2(Fan)/+ ;AR L2/Y mice compared to AR L2/Y mice. However, Pax7 CreERT2(Gaka)/+ ;AR L2/Y ;R26 tdTomato/+ mice showed no significant differences between control and mutant muscle regeneration. These findings indicate that AR in satellite cells is not essential for muscle regeneration. We propose that Pax7 CreERT2(Fan)/+ control mice should be included in all experiments, because these mice negatively affect the muscle regeneration and show the mild regeneration phenotype.